1987
DOI: 10.1007/bf02371036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbicides Lindex and Simazine on chloroplast and nodule development, nodule activity, and grain yield inLupinus albus L.

Abstract: Field and laboratory investigations were carried out to determine the influence of two commercial herbicides Lindex and Simazine on symbiotic N2 fixation, the photosynthetic apparatus, percentage of proteins, and grain yield of lupins (Lupinus albus L. cv. Multolupa). The herbicides were added (3 kg commercial product in 9001 per ha) two weeks after sowing. The nodulated roots were tested for nitrogenase activity by the acetylene reduction assay (ARA) at the first and second flowering. The ARA values decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Kumar et al (1981) reported poor nodulation in chickpea with 1.6 and 3.2 kg/ha each of simazine and prometryn. Simazine at 1.38 kg/ha markedly decreased the specific nitrogenase activity in lupins (De Felipe et al, 1987), while Kumar et al (1981) could not detect nitrogenase activity in simazine-treated (at 1.6 and 3.2 kg/ha) chickpea plants, as leghaemoglobin did not develop at all in the nodules. Bentazone is known to decrease specific nitrogenase activity in kidney bean (Bethlenfalvay et al, 1979;Schnelle and Hensley, 1990) and soybean (Ozair and Moshier, 1988;Yueh and Hensley, 1993).…”
Section: Effects Of Herbicidesmentioning
confidence: 82%
See 3 more Smart Citations
“…Kumar et al (1981) reported poor nodulation in chickpea with 1.6 and 3.2 kg/ha each of simazine and prometryn. Simazine at 1.38 kg/ha markedly decreased the specific nitrogenase activity in lupins (De Felipe et al, 1987), while Kumar et al (1981) could not detect nitrogenase activity in simazine-treated (at 1.6 and 3.2 kg/ha) chickpea plants, as leghaemoglobin did not develop at all in the nodules. Bentazone is known to decrease specific nitrogenase activity in kidney bean (Bethlenfalvay et al, 1979;Schnelle and Hensley, 1990) and soybean (Ozair and Moshier, 1988;Yueh and Hensley, 1993).…”
Section: Effects Of Herbicidesmentioning
confidence: 82%
“…Thus, the plants were dependent for nodulation on the native strains of Rhizobium in the soil. The higher nitrogenase activity found at some sampling dates in the unweeded treatment compared to the hand-weeded treatment might be due to the reasons proposed by De Felipe et al (1987) and Brockwell et al (1995).…”
Section: Effects Of Weedsmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar results reported by Singh and Wright (2002) that the adverse effect of herbicides on nodulation and nitrogen fixation in legumes by affecting the nitrogen-fixing Rhizobia (Rhizobium leguminosarum population). Whereas, Felipe et al, (1987) suggested that, the direct effects of herbicides on the plant, decreased the number of nitrogen-fixing bacteroids.…”
Section: Resultsmentioning
confidence: 99%